The Role of the Insulin/IGF System in Cancer: Lessons Learned from Clinical Trials and the Energy Balance-Cancer Link - Bowers, Laura W.; Rossi, Emily L.; O’Flanagan, Ciara H.; deGraffenried, Linda A.; Hursting, Stephen D. (Frontiers in Endocrinology, 2015)
Numerous epidemiological and pre-clinical studies have demonstrated that the insulin/insulin-like growth factor (IGF) system plays a key role in the development and progression of several types of cancer. Insulin/IGF signaling, in cooperation with chronic low-grade inflammation, is also an important contributor to the cancer-promoting effects of obesity. However, clinical trials for drugs targeting different components of this system have produced largely disappointing results, possibly due to the lack of predictive biomarker use and problems with the design of combination therapy regimens. With careful attention to the identification of likely patient responders and optimal drug combinations, the outcome of future trials may be improved. Given that insulin/IGF signaling is known to contribute to obesity-associated cancer, further investigation regarding the efficacy of drugs targeting this system and its downstream effectors in the obese patient population is warranted.